Structural, optical and magnetic properties of Cr-substituted CeO2 nanoparticles - Alla S.K.; Prasadarao Komarala E.V.; Mandal R.K.; Prasad N.K. (My University, 2025)
Nanocrystalline CrxCe1−xO2 (0 ≤ x ≤ 0.3) samples were synthesized by a microwave refluxing method. These samples were characterized by X-ray diffractometer, Transmission electron microscope, Raman spectroscopy, UV-Vis spectrometer, Photoluminescence, and X-ray photoelectron spectroscopy. The XRD and TEM analyses indicates the formation of single phase in them. UV-vis spectroscopy results displayed blue shift of absorption peaks with increased Cr content. Magnetic measurements showed initial increase followed by decrease of saturation magnetization (MS) with increasing doping concentration. The MS value of x = 0.05 is nearly four times larger than that of undoped CeO2. This initial enhancement of MS has been attributed to the creation of oxygen vacancies. The decrease in MS at higher concentrations, has been corroborated with the appearance of antiferromagnetic interaction above a threshold value of Cr3+ content which is lying between x = 0.05 and 0.1. © 2016 Elsevier B.V.